Pesan Dakwah Dalam Acara Adat Sedekah Dusun Pada Masyarakat Desa Pangkul Kecamatan Cambai Kota Prabumulih - Sisi Yola Rizka; Hamidah; Muslimin (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research is entitled "Da'wah Messages in the Hamlet Alms Traditional Event in the Community of Pangkul Village, Cambai District, Prabumulih City". This research aims to find out the procedures for implementing the Dusun Alms Traditional Event and the da'wah messages contained therein. Before holding the Dusun Alms Traditional Event for the people of Pangkul Village, Cambai District, Prabumulih City, and knowing the message of preaching in the Dusun Alms traditional event. Where there is a message of da'wah in this traditional event. To achieve this goal, descriptive qualitative writing was chosen. In analyzing an object as a means of reference to obtain clearer data by collecting data through observation and in-depth interviews with a number of informants, namely: village government, religious leaders, traditional leaders. The results of the writing show the implementation of traditional events and da'wah messages contained in the traditional Alms Dusun event. In the implementation of the Dusun Sedekah traditional event there is a series of events, namely: cooking dodol/juadah, slaughtering buffalo/cows/goats/chickens, containing a da'wah message to always strengthen friendship, the tradition of Kuda Lumping on the evening before the Dusun Alms, the Puyang Pangkul pilgrimage ritual on in the morning, the Dusun Alms Ritual at the Traditional Hall, reading the Yasin letter together, eating together, blenger, contains a message of da'wah which aims to ask for blessings and sanjo (silaturahmi).